DNA‐Hybrid‐Gated Multifunctional Mesoporous Silica Nanocarriers for Dual‐Targeted and MicroRNA‐Responsive Controlled Drug Delivery1. Issue 9 (27th January 2014) - Zhang, Penghui; Cheng, Fangfang; Zhou, Ri; Cao, Juntao; Li, Jingjing; Burda, Clemens; Min, Qianhao; Zhu, Jun‐Jie
Abstract The design of an ideal drug delivery system with targeted recognition and zero premature release, especially controlled and specific release that is triggered by an exclusive endogenous stimulus, is a great challenge. A traceable and aptamer‐targeted drug nanocarrier has now been developed; the nanocarrier was obtained by capping mesoporous silica‐coated quantum dots with a programmable DNA hybrid, and the drug release was controlled by microRNA. Once the nanocarriers had been delivered into HeLa cells by aptamer‐mediated recognition and endocytosis, the overexpressed endogenous miR‐21 served as an exclusive key to unlock the nanocarriers by competitive hybridization with the DNA hybrid, which led to a sustained lethality of the HeLa cells. If microRNA that is exclusively expressed in specific pathological cell was screened, a combination of chemotherapy and gene therapy should pave the way for a targeted and personalized treatment of human diseases.